Analisis Pengaruh Perbandingan Koil Standar, Koil Imitasi, dan Koil Racing Terhadap Kinerja Sepeda Motor Dengan Kapasitas Mesin 160 CC - Muhammad Ranay; Muhammad Rasid; Ali Medi (PT. Hasba Edukasi Mandiri, 2025)
The coil function to convert low voltage into high voltage, which produces a spark in the spark plug. This is important for efficient combustion. In this experimental research, we analyzed the effect of comparing standard coils, imitation coils and racing coils on the performance of motorbikes with an engine capacity of 160 cc. Performance tests are carried out using the Dyno Test tool to measure torque, power and motor acceleration. In terms of torque performance (Nm), data showed that the highest performance was found in tests with a standard coil of 34.16 Nm, while the racing coil was 29.79 Nm and the imitation coil was 26.50 Nm. In terms of power performance (HP), data was obtained that the highest performance was found in tests with a racing coil of 24.5 HP, while the standard coil was 23.1 HP and the imitation coil was 21.6 HP. In terms of acceleration performance (s), data shows that motorbike acceleration using a standard coil to reach peak performance or speed (topspeed) takes 6.34 seconds, a racing coil takes 5.64 seconds and an imitation coil takes 5.82 seconds.